Butlers and dish‐bearers in Anglo‐Saxon courts: household officers at the royal table1. Issue 248 (23rd March 2017) - Gautier, Alban
Abstract: In Anglo‐Saxon courts, from the eighth century down to the Norman conquest, 'officers of the mouth', bore household titles and served the king and his guests during meals, at least on major occasions. Those butlers ( pincernae ) and dish‐bearers ( dapiferi, disciferi ) were not mere 'waiters' but members of great aristocratic families; serving the king's table was an honour for them, with all the implications of that word in an early medieval context. Using a variety of sources, particularly the subscription lists of charters, this article examines their rank at court, social origin, degree of proximity to kings and queens, and the nature of their occupation.